A New Species of the Genus Proctophyllodes (Analgoidea, Proctophyllodidae) from Golden Oriole - Burdejnaja, S.J.; Kivganov, D.A. (Вестник зоологии, 2011)
The species Proctophyllodes orioli Burdejnaja et Kivganov, sp. n. from Golden Oriole Oriolus oriolus Linnaeus, 1758 (Passeriformes) was described (Zmiinyi Island, Ukraine). New species belonging to the group of species “musicus”, is morphologically close to P. dasyxiphus Atyeo et Braasch, 1966 from (Eastem) Black-Headed Oriole Oriolus larvatus Lichtenstein, 1823. С иволги, Oriolus oriolus Linnaeus, 1758 (Passeriformes), описан новый вид Proctophyllodes orioli Burdejnaja et Kivganov, sp. n. (Украина, о. Змеиный), принадлежащий к группе видов «musicus». Описанный вид морфологически близок к P. dasyxiphus Atyeo et Braasch, 1966 с африканской черноголовой (масковой) иволги Oriolus larvatus Lichtenstein, 1823.